Nutritional profile and presence of risk factors and protection for non-communicable chronic diseases in diabetics - doi 10.4025/actascihealthsci.v34i2.8886 - Francielli Aparecida Garcia da Costa; Giana Zarbato Longo (Universidade Estadual de Maringá, 2012)
This study aimed to delineate the nutritional profile and to investigate the presence and distribution of factors of risk and protection for Non-Communicable Diseases (NCD) in diabetic participants. For this, 54 individuals of both sexes participated in this study, aged 28 to 87 years who have been attended by a health center of the municipality of Maringá, Paraná State. It was measured the weight, height and waist circumference and applied two questionnaires related to risk factors and food frequency (FFQ) respectively. The study design is cross-sectional and the descriptive analysis was performed using the statistical software Epi info version 3.32 (2005). The results showed that the most relevant risk factors in the diabetic population in relation to NCD have been related to the overweight, lack of physical activity and self-reported hypertension. The protection factors were healthy diet and quitting of smoking. Based on nutritional assessment, the BMI (Body Mass Index) and waist circumference have been positively correlated with high significance. Health education is necessary for the prevention and health promotion of these individuals through the change of lifestyle.